Movement, residency, and behavioral plasticity of reef manta rays in the Samarai Islands of Papua New Guinea - Anna M. Knochel; Joanna L. Harris; Shannon E. Murphy; Annie Murray; Guy M.W. Stevens; Mark V. Erdmann (PLoS ONE, 2026)
The reef manta ray ( Mobula alfredi ) is a highly mobile pelagic marine ray found throughout the tropical and subtropical waters of the Indo-Pacific, but investigation into their behavior and ecology within Papua New Guinea has not been previously undertaken. Furthermore, the home range, dispersal characteristics, and inter-seasonal fine-scale habitat use of this species is limited. To address these data gaps and investigate the vertical and horizontal habitat use of a previously unstudied population, SPLASH10-F-321A pop-off archival satellite tags were used to track ten adult individuals from 4–181 days between 2016–2018 across two distinct monsoonal periods in the Samarai Islands of Milne Bay, southeastern Papua New Guinea. Our findings indicate strong site-attached movement patterns for reef manta rays in this region, with 75% of relocations occurring within ten kilometers of the tagging site. While occasional movements beyond this range were observed, the maximum displacement distance was 86.9 km, and no consistent seasonal differences in horizontal displacement distance were detected. Tagged rays displayed a clear preference for the Samarai Islands and the Papuan Plateau across both monsoons, with shallow bathymetry and elevated chlorophyll-a values driving observed habitat preferences. We found evidence for shifts in vertical occupancy of the water column that corresponded with the mixed layer depth; dives were deeper when the mixed layer depth was shallow, suggesting that reef manta rays can exhibit behaviorally plastic responses to seasonal variations in oceanographic conditions. These findings provide the first insight into the movement ecology of this reef manta ray population that can be used to inform the development of economically valuable manta ray tourism practices and a sustainable management plan in the region.